Mapping of Evacuation Paths and Gathering Points in Efforts to Reduce Disaster Risk in Taman Baru Village Sekotong West Lombok to Create a Disaster-Responsive Village - Suripto; Wahyu Kurniawan; Usamah Mashadi (Universitas Mataram, 2022)
Taman Baru Village, Sekotong, West Lombok Regency is one of the areas under a hill valley and surrounded by hills with a height of about 0-1000 meters above sea level. The average level of rainfall in this area is 1381 mm with an average number of rainy days of 120 days so that this area is often affected by disasters, such as floods and landslides. Therefore, the Taman Baru Village needs to be wary of, considering that disasters can happen at any time. Thus, it is necessary to have disaster mitigation, namely the mapping of evacuation routes and gathering points and their visualization. These goals of this program are the existence of evacuation routes and gathering points, which are devoted to tidal floods, earthquakes and landslides. The results of this work program are also expected to be the best means that can facilitate the community in evacuating themselves when a disaster occurs. These output of this activity were a disaster mitigation leaflet in Taman Baru Village, a map of evacuation routes and gathering points in Taman Baru Village and their visualization (installation of evacuation route signs and gathering points that can provide instructions for people who want to evacuate themselves in the event of a disaster). The outcome of this activity is the increased awareness and understanding of the people of Taman Baru Village on disaster mitigation, especially earthquakes, tsunamis, landslides and floods